Response of primary production and biomass allocation to nitrogen and water supplementation along a grazing intensity gradient in semiarid grassland - Gong, Xiao Ying; Fanselow, Nicole; Dittert, Klaus; Taube, Friedhelm; Lin, Shan (European journal of agronomy, 2015)
•We performed a grazing experiment with water and N fertilizer additions in a steppe.•No evidence for grazing optimization on primary production was found in this study.•Grazing decreased the belowground fraction of net primary production (BNPP/NPP).•Water and N additions significantly increased aboveground net primary production.•The “whole-plant” perspective in studying plant–herbivore interactions was highlighted. Herbivory and resource availability interactively regulate plant growth, biomass allocation, and production. However, the compensatory growth of plants under grazing intensities and manipulated environmental conditions is not well understood. A 2-year experiment with water (unirrigated and irrigated) and nitrogen fertilizer (0 and 75kgNha−1year−1) addition was conducted at sites with 4 grazing intensities (0–7 sheepha−1) in an annually rotational grazing system in Inner Mongolia. In this study, grazing had no significant effect on aboveground net primary production (ANPP) and net primary production (NPP). However, high grazing intensity strongly reduced the fraction of belowground net primary production to NPP. Water and nitrogen additions significantly increased ANPP by 39% and by 23%, respectively, but had no effect on belowground net primary production. ANPP showed lower response to nitrogen addition at high grazing intensity sites than at low grazing intensity sites. We found no evidence for grazing optimization on primary production of semiarid steppe, regardless of resource supplementations. Grazed plants minimized the reduction of ANPP by altering allocation priority and morphological traits. Our study highlights the “whole-plant” perspective when studying plant–herbivore interactions.